Analisis Faktor-Faktor Yang Mempengaruhi Belanja Daerah Kabupaten/Kota Provinsi Nusa Tenggara Timur Tahun 2015-2019 - Ainun Ningsih Nasution; Dwi Susilowati (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of Regional Taxes, Regional Retribution, Special Allocation Funds, and the amount on District / City Regional Expenditure in East Nusa Tenggara Province for 2015 – 2019. In this study, researchers used a sampling technique whit a sampling method, amounting to 21 districts and one city, using panel data. In this study, the fixed effect method is the best model. The results of this study are local taxes, special allocation funds, and total population have a positive and significant effect on regional spending in East Nusa Tenggara Timur Province. In contrast, local charges positively and significantly affect provincial expenditure on East Nusa Tenggara Province.